If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 4)(6x + -8) = 0 Reorder the terms: (4 + 2x)(6x + -8) = 0 Reorder the terms: (4 + 2x)(-8 + 6x) = 0 Multiply (4 + 2x) * (-8 + 6x) (4(-8 + 6x) + 2x * (-8 + 6x)) = 0 ((-8 * 4 + 6x * 4) + 2x * (-8 + 6x)) = 0 ((-32 + 24x) + 2x * (-8 + 6x)) = 0 (-32 + 24x + (-8 * 2x + 6x * 2x)) = 0 (-32 + 24x + (-16x + 12x2)) = 0 Combine like terms: 24x + -16x = 8x (-32 + 8x + 12x2) = 0 Solving -32 + 8x + 12x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(-8 + 2x + 3x2) = 0 Factor a trinomial. 4((-2 + -1x)(4 + -3x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333Solution
x = {-2, 1.333333333}
| 8x+70=9x+69 | | 2y-6x=-3 | | 7K+3=K+13 | | 3y-4(-4y-18)=-118 | | 2/3+2=4/3+1/3 | | 19=.8(20x+16)-14x | | 1.05p=31.5 | | 20w+100=280 | | 2d^2+7d=0 | | 6v(2v-3)= | | 4q-72=q+24 | | 13+6z=7(z-1) | | 3(4x-9)=29 | | 4x^3+12x^2+16=0 | | 3c+47=9c+41 | | 4(5)+y=24 | | 100y-2x=0 | | 15b=7b+40 | | 3p-1-2x+9=0 | | 19t+31=2t+65 | | r^2=88 | | 6h+8=26 | | 10y-2x=5 | | -1[7x+6(x+1)]=-4x-6 | | 2y-30=3y-54 | | (11x-25)+(24+10)=90 | | 3+10b-5-4b= | | 3y+8=y+66 | | -48=5c-2 | | 2x^2-13=11 | | 0.12x+1=0.880 | | 2y=y+50 |